Barriers to uptake of antimicrobial advice in a UK hospital: a qualitative study. Issue 4 (August 2016) - Broom, J.; Broom, A.; Plage, S.; Adams, K.; Post, J.J.
Summary: Background: The role of infectious diseases (ID) and clinical microbiology (CM) in hospital settings has expanded in response to increasing antimicrobial resistance, leading to widespread development of hospital antimicrobial stewardship (AMS) programmes, the majority of which include antibiotic approval systems. However, inappropriate antibiotic use in hospitals continues, suggesting potential disjunctions between technical advice and the logics of antibiotic use within hospitals. Aim: To examine the experiences of doctors in a UK hospital with respect to AMS guidance of antibiotic prescribing, and experiences of a verbal postprescription antibiotic approval process. Methods: Twenty doctors in a teaching hospital in the UK participated in semi-structured interviews about their experiences of antibiotic use and governance. NVivo10 software was used to conduct a thematic content analysis systematically. Findings: This study identified three key themes regarding doctors' relationships with ID/CM clinicians that shaped their antibiotic practices: (1) competing hierarchical influences limiting active consultation with ID/CM; (2) non-ID/CM consultants' sense of ownership over clinical decision-making and concerns about challenges to clinical autonomy; and (3) tensions between evidence-based practice and experiential-style learning. Conclusions: This study illustrates the importance of examining relations between ID/CM and non-ID/CM clinicians in the hospital context, indicating that AMS models that focus exclusively on delivering advice rather than managing interprofessional relationships may be limited in their capacity to optimize antibiotic use. AMS and, specifically, antibiotic approval systems would likely be more effective if they incorporated time and resources for fostering and maintaining professional relationships.